If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(11 + -1w) = 3(3w + -9) (11 * 3 + -1w * 3) = 3(3w + -9) (33 + -3w) = 3(3w + -9) Reorder the terms: 33 + -3w = 3(-9 + 3w) 33 + -3w = (-9 * 3 + 3w * 3) 33 + -3w = (-27 + 9w) Solving 33 + -3w = -27 + 9w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-9w' to each side of the equation. 33 + -3w + -9w = -27 + 9w + -9w Combine like terms: -3w + -9w = -12w 33 + -12w = -27 + 9w + -9w Combine like terms: 9w + -9w = 0 33 + -12w = -27 + 0 33 + -12w = -27 Add '-33' to each side of the equation. 33 + -33 + -12w = -27 + -33 Combine like terms: 33 + -33 = 0 0 + -12w = -27 + -33 -12w = -27 + -33 Combine like terms: -27 + -33 = -60 -12w = -60 Divide each side by '-12'. w = 5 Simplifying w = 5
| 5+8v-8v-4=v-7 | | 2x+6-1=7x | | a=-5a+6a | | 25r^2-9=0 | | 3(1-2x)+4(2x-5)=7 | | -14=7(3+5v)-6(-6-6v) | | x/9+7=3 | | 3y-7=27+y | | 6v+6-7v=7 | | 6=-3(5x-7) | | 5=a(2)+3(2) | | 34x-18=10x-9 | | 12x^2=15x-3 | | 3(2x-8)=2(2x+4)-12 | | 55=5(1-5x) | | 5m-10=-45 | | 3(x-2)+6=24 | | 9=5+4x | | k^2+k-45=0 | | 5k-26=-6(4k-4)-6k | | -3x=28 | | -8(x+6)=12-6(x-2) | | 46.2*10-2=X | | 13=5+x | | -4(6n+8)=8n | | 0=8-3x | | p(6+5-7)=20 | | x-2x=-4 | | 15u^5+38u^4+18u^3=0 | | 2c+11=7 | | 0.5x+3.5x-x=9 | | -14+x=6 |